Particularities of an incremental forming application in multi-layer construction elements - Petek, Aleš (Strojniški vestnik, 2009)
The technologies for low quantity production of sheet metal components and parts have expanded greatly in recent years. They are applied mostly for thin single metal sheets. However, such technologies could also be interesting to form individual multi-layer construction elements. As such construction elements consists of metal plates that are usually hot zinced and painted before forming process, it is necessary to select an appropriate technology with stable process parameters to avoid any damages. In this article, particularities of an incremental forming application as additional technology in multi-layer construction element production are presented. Special attention is dedicated to the forming principles, the forming influences on the mechanical properties of the multi layer element and the corrosion of the locally deformed coloured metal plate. The latter two activities represent the most important requirements in order to fulfil construction standards and due dates, both independently of unpredictable sharp weather conditions. It was discovered that the statics of the multi-layer element improves if appropriate shape parameters in connection with process parameters are applied, where the painted layer remains undamaged, even after demanding anticorrosion tests.
Keywords: konstrukcijski elementi; preoblikovanje kovin; pločevina; statika; korozija